2015
DOI: 10.1299/transjsme.15-00180
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of brain activity during local hot-cold stimulus using near-infrared spectroscopy (Analysis of brain activity during pain stimulus by cold stimulus)

Abstract: Methods such as the Predicted Mean Vote and Standard New Effective Temperature were developed to evaluate thermal comfort. However, radiation and convection of heat due to factors such as sunlight or air cycle are strong in indoor environments. Moreover, the thermal environment in such indoor environment is non-uniform and locally inhomogeneous, which makes evaluation thermal comfort difficult. We aim to evaluate the local thermal environment by analyzing brain activity. The final goal is to develop an air con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Moreover, the researchers reported that cold water significantly decreased activity in the θ (4.0 -8.0 Hz) and α1 bands after presentation, compared with warm water [7]. Regarding the relationship between cerebral blood flow and thermal stimulation, Hou et al [8] reported that cerebral blood flow in the frontal lobe during the presentation of local hot-cold stimuli to the hand using an aluminum plate exhibited increased or decreased oxy-Hb under specific temperature conditions. With hot stimulation, oxy-Hb decreased at 39 °C and increased at 45 °C [8].…”
Section: Previous Studies On Brain Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the researchers reported that cold water significantly decreased activity in the θ (4.0 -8.0 Hz) and α1 bands after presentation, compared with warm water [7]. Regarding the relationship between cerebral blood flow and thermal stimulation, Hou et al [8] reported that cerebral blood flow in the frontal lobe during the presentation of local hot-cold stimuli to the hand using an aluminum plate exhibited increased or decreased oxy-Hb under specific temperature conditions. With hot stimulation, oxy-Hb decreased at 39 °C and increased at 45 °C [8].…”
Section: Previous Studies On Brain Activitymentioning
confidence: 99%
“…Regarding the relationship between cerebral blood flow and thermal stimulation, Hou et al [8] reported that cerebral blood flow in the frontal lobe during the presentation of local hot-cold stimuli to the hand using an aluminum plate exhibited increased or decreased oxy-Hb under specific temperature conditions. With hot stimulation, oxy-Hb decreased at 39 °C and increased at 45 °C [8]. Taken together, the studies described above suggest that brain activity varies depending on the presentation temperature.…”
Section: Previous Studies On Brain Activitymentioning
confidence: 99%
See 1 more Smart Citation